The Doctrinal Investigations of what is Included in the Conditional (If) in the Holy Qur’an Surat Al-Takwir as A Model (Islamic Sciences Journal, 2023)
ABSTRACT                         The glorious Qur’an paid a great attention to the doomsday and lots of Qur’anic verses showed that importance and its valuable issues; .You hardly pass through any surah of the Qur’an, unless you find in it a conversation about the day of resurrection, and what will happen in that day including conditions and horrors. In various ways, including what was mentioned in the (if) conditional answers, where the condition came as an opening to seven chapters, including Surat Al-takwir, This surah shares several characteristics with others, including: that in most of these surahs there is a talk about the doomsday and its introductions, for this importance, the  research topic came under the title: The Doctrinal Investigations of What If The Conditional Included from The Glorious Quran - Surat Al-Takwir As A Model. The academic subject matter enforced our research to be based on a preface, an introduction, and two chapters, followed by a conclusion and a list of references. Several demands are required in the definition of the title and its vocabulary, then the first topic included: The horrors of the pre- Doomsday, led by the conditional “if” in Surat Al-takwir, and the second included: The horrors after the Doomsday, which is led by the conditional “if” in Surat Al-takwir.